Thermophysical and stability investigation of Al2O3- TiO2/water hybrid nanofluids - Barlin Barlin; Amir Arifin; Astuti Astuti; Irvandy Irvandy; Irvandi Pratama Putra; Hary Putranto (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2023)
Currently, one of the big challenges in the cooling systems technology is producing coolant fluid with good thermophysical dan stability properties. The new cooling fluids, namely nanofluid-based coolant has been developed for facing this challenge. Nanofluid is the dispersion of nanoparticle into base fluid. In this experimental investigation, thermophysical and stability of Al2O3-TiO2/Water hybrid nanofluid are studied. The Al2O3-TiO2/Water based hybrid nanofluid have been prepared by using two step method. The experiment is carried out for the various combination of volume fraction (0.2-0.6 wt%), ratio of nanoparticles (70:30-30:70wt%), stirring time (30-90 min), and sonication time (60-120 min). The thermophysical properties of the prepared nanofluids were characterized using pycnometer method for density and viscometer fall ball for viscosity. Photograph capturing method is applied to investigate the stability of nanofluids. According to the obtained results, the viscosity, density and stability have influenced by the synthesis parameters.